اعلیٰ حضرت اور علامہ اقبال کا شان رسالت مآب ﷺ میں شعری مشترکات کا تقابلی جائزہ: A Comparative Study of the Poetic Commonalities Between Ala Hazrat and Allama Iqbal in Praise of the Holy Prophet Muhammad (Peace Be Upon Him) - Hafiz Muhammad Abdullah; Hanzla Mukhtar (International Research Journal of Arabic and Islamic Studies, 2024)
This research presents a comparative analysis of the poetic expressions of Ala Hazrat Ahmed Raza Khan Barelvi and Allama Muhammad Iqbal in praise of the Holy Prophet Muhammad (Peace Be Upon Him). Both poets, despite their differing socio-political and theological backgrounds, exhibit deep reverence and love for the Prophet ﷺ in their poetry. The study highlights the shared themes in their works, such as devotion to the Prophet ﷺ, his unique status in creation, his mercy to the worlds, and his spiritual centrality in Islam. By examining selected verses from both poets, this paper uncovers how their poetic language, imagery, and metaphors converge in expressing profound respect and attachment to the Prophet ﷺ. The analysis also reflects on how their praise not only serves as literary devotion but also as a means to reinforce the spiritual and moral dimensions of Islamic thought. This study aims to bridge a better understanding of the harmonious elements in Islamic poetic traditions across different intellectual spectrums.